2004
DOI: 10.1017/s0263034604221139
|View full text |Cite
|
Sign up to set email alerts
|

Solutions of the nonlinear paraxial equation due to laser plasma–interactions

Abstract: This article presents a numerical and theoretical study of the generation and propagation of oscillation in the semiclassical limit ħ → 0 of the nonlinear paraxial equation. In a general setting of both dimension and nonlinearity, the essential differences between the “defocusing” and “focusing” cases are observed. Numerical comparisons of the oscillations are made between the linear (“free”) and the cubic (defocusing and focusing) cases in one dimension. The integrability of the one-dimensional cubic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…However, after the experiments of Badziak et al~1999, 2003Badziak et al~1999, , 2004aBadziak et al~1999, , 2004b! and the theory of the skin layer acceleration~Hora et Hora, 2003;Miley et al, 2003Miley et al, , 2004Osman et al, 2004aOsman et al, , 2004bHora, 2004!, the ps laser pulses in the TW to few PW range may provide the conditions A and B as explained in Section 4.…”
Section: Fusion Energymentioning
confidence: 99%
“…However, after the experiments of Badziak et al~1999, 2003Badziak et al~1999, , 2004aBadziak et al~1999, , 2004b! and the theory of the skin layer acceleration~Hora et Hora, 2003;Miley et al, 2003Miley et al, , 2004Osman et al, 2004aOsman et al, , 2004bHora, 2004!, the ps laser pulses in the TW to few PW range may provide the conditions A and B as explained in Section 4.…”
Section: Fusion Energymentioning
confidence: 99%
“…There has been important work on the solution of the time-dependent nonlinear paraxial equation [Osman et al, 2000[Osman et al, , 2004, corresponding to laser plasma interaction, presenting numerical and theoretical studies in the semiclassical limit. The essential differences between the focusing and defocusing cases were investigated for an arbitrary nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Using the formalism of Akhmanov et al [1968] and its extension by Sodha et al [1974, 1976] as well as the radial distribution of the dielectric function (as indicated in the preceding paragraph), the self‐focusing of an electromagnetic Gaussian beam in the ionosphere has been investigated in the paraxial approximation. There has been important work on the solution of the time‐dependent paraxial [ Osman et al , 2000, 2004] or nonlinear Schrödinger's equation with particular reference to solitons [ Beech and Osman , 2005]; however, this has not been made use of in the present investigation on account of the fact that the present analysis is confined to the steady state.…”
Section: Introductionmentioning
confidence: 99%